Singapore’s economic development: Pro- or anti-Washington consensus - PENG, Nathan (Institutional Knowledge at Singapore Management University, 2018)
Singapore’s remarkable economic development in the past five decades since independence has attracted much policy attention. This article first provides a brief overview of Singapore’s economic development. The second part discusses Singapore’s development strategies that are aligned with the Washington Consensus: globalisation, conservative fiscal and monetary policies, investments in education and infrastructure. It also discusses the policies adopted to further enhance the outcomes of such policies. The third part focusses on policies that are inconsistent with the prescriptions of the Washington Consensus: the visible hand of government direction of industry, the important role of state-owned enterprises, as well as growth-enhancing social policies. It concludes with the present challenges facing the city-state.